Erosion resistance performance of marine concrete with red mud, slag and fly ash - Hailong Wang; Yulan Wang; Xiaofan Wang; Qianlong Jin; Yucheng Wu; Yihe Qu; Zhenlong Zhao (Case Studies in Construction Materials)
The effects of slag (GGBS), red mud (RM) and fly ash (FA) on the erosion resistance and microstructure of concrete in seawater were investigated. The effects of adding industrial waste admixtures on the compressive and flexural strengths of concrete 15 % NaCl, 15 % Na₂SO₄, 15 % MgCl₂, and 15 % MgSO₄ environments were examined. The impact of these admixtures on mass loss in concrete subjected to freeze-thaw cycles in seawater was also evaluated. The results indicate that utilizing varying proportions of FA, RM, and GGBS to partially replace OPC under seawater conditions improved the unconfined compressive strength at all curing ages. The 28-day strength exhibited a decreasing trend with higher RM/GGBS ratios. Under high concentrations of chloride and sulfate ions, the strength enhancement effect of S4 diminishes, while Mg²⁺ appear to suppress the synergistic effects of industrial by-products in S5-S7. Using industrial by-products instead of cement can reduce the freezing and thawing quality loss of 9.71–73.01 % in seawater. When FA, RM and GGBS were combined, the freeze-thaw resistance was increased by more than 60 %. Microscopic analysis reveals that S4 and S5 exhibit more abundant hydration products and a refined pore structure, leading to superior mechanical performance in seawater and corrosive environments.